Chroman-4-ones via Microwave-Promoted Domino Claisen Rearrangement–Oxa-Michael Addition: Synthesis of Tabchromones A and B - Schmidt, Bernd; Riemer, Martin; Schilde, Uwe (Synlett, 2014)
Allyl phenyl ethers with a pendant enone substituent undergo, upon microwave irradiation, a domino sequence of Claisen rearrangement and 6-endo-trig-cyclization to furnish functionalized chroman-4-ones. The natural products tabchromones A and B were synthesized via this method.
Keywords: cyclization; Michael addition; rearrangement; tandem reaction; Wacker reaction